2011
DOI: 10.1007/s00464-011-1991-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic rectal resection for severe endometriosis of the mid and low rectum: technique and operative results

Abstract: Laparoscopic resection of the mid/low rectum for endometriosis can be performed safely with acceptable rates of morbidity/reoperation and with low rates of specific complications, including anastomotic leak and rectovaginal fistula. The very high surgical volume of the operating surgeon is probably one of the most important factors in order to maximize postoperative outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 19 publications
4
52
1
4
Order By: Relevance
“…The two major complications of the surgical treatment of intestinal DIE are anastomotic leakage and rectovaginal fistula [15, 16, 1921]. Anastomotic dehiscence and leakage seem to occur after segmental bowel resection in 3% to 7% of cases and up to 20% in low rectal anastomosis [22, 23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The two major complications of the surgical treatment of intestinal DIE are anastomotic leakage and rectovaginal fistula [15, 16, 1921]. Anastomotic dehiscence and leakage seem to occur after segmental bowel resection in 3% to 7% of cases and up to 20% in low rectal anastomosis [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…In the systematic review conducted by Meuleman et al [19] including 2036 women undergoing segmental bowel resection for intestinal DIE the rates of rectovaginal fistula and anastomotic leakage were 2.7% and 1.5%, respectively. In the large series of Ruffo et al [16], laparoscopic resection of the mid/low rectum for deep infiltrating endometriosis was conducted in 750 women and the rates of anastomotic leak and rectovaginal fistula were 3% and 2%, respectively. Temporary ileostomy rate was 14.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Primum non nocere. furthermore, as pointed out by Drs Bailey and snyder, disease involving the level of the cul de sac is common, and we have found that this is well within reach of a finger to permit combined laparoscopic and digital palpation to assess the extent of rectal involvement.…”
mentioning
confidence: 99%
“…4 Primum non nocere. 3 as demonstrated with our disc experience, the majority of patients can be spared the morbidity of the full rectal mobilization that risks rectal denervation.…”
mentioning
confidence: 99%